Linking net foreign portfolio debt and equity to exchange rate movements - Malin Gardberg (Research Institute of Industrial Economics (IFN), 2018)
Many currencies, especially those of countries with negative net foreign assets, tend to depreciate during times of financial turbulence. Using a panel of 26 currencies over the period 1/1997 - 6/2016, I show that the composition of net foreign assets matter for the exchange rate sensitivity to changes in global financial market risk tolerance, where debt financing increases it and equity financing reduces it. Thus, currencies of countries with large negative net external portfolio debt are more vulnerable to changes in financial market uncertainty than currencies with the equivalent net external equity. Ownership matters too, private net foreign debt liabilities heighten the exchange rate sensitivity much more than public. The relationship between banking sector risk intolerance, net external asset positions and exchange rates has, moreover, become stronger since the credit crisis.
Keywords: F31; F32; G15; G20; C23; 330; Exchange rates; Excess currency returns; Net foreign assets; External imbalances; Net foreign portfolio debt; Financial market risk tolerance; Panel data